A Data Mining Study on League of Legends - Tanyildizi, Erkan; Yildirim, Gokce; Kaya, Ogun Can (Institute of Electrical and Electronics Engineers Inc., 2019)
The popularity of computer games is increasing with developing technology. Online games, where people interact with each other, are particularly preferred. Among the online games, League of Legends is one of the paced and highly competitive games. In such games, the champion's choices stages and selection restrictions are important. Data analysis should be performed well in order to predict the result of the game. Data mining methods can be used in data analyzes. In this study, the effect of the choices, restrictions and in-game events in future games on winning or losing the game will be predicted. Some of the classification algorithms have applied to the data set. As a result of the studies, it was determined that there is a connection between the player's choices and the winning or losing of the game. © 2019 IEEE.
League of Legends Oyunu Üzerine Bir Veri Madenciligi Çalismasi
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: Classification Algorithms; Data mining; Decision Trees; League of Legends